UMP, MBK collaborate in effective management of traffic and public transport systems - Mimi Rabita, Abdul Wahit (2022)
KUANTAN, 30 March 2022 - Universiti Malaysia Pahang (UMP) will collaborate with the Kuantan City Council (MBK) in sharing expertise to improve traffic management efficiency and public transport management in line with the development of smart and sustainable cities especially involving cities with high mobility and pedestrian-friendly levels.